Machinability improvement in end milling of Titanium Alloy Ti-6Al-4V through preheating - Amin, A. K. M. Nurul; Ginta, Turnad Lenggo (IIUM Press, 2011)
Titanium alloys are used widely in the aerospace, chemical and ship building industry because of their superior mechanical properties, heat resistance and corrosion resistance. Titanium alloys, however, are materials that are extremely difficult to machine. During the machining of titanium alloy, tool wear progresses rapidly because of the high cutting temperature and strong adhesion between the tool and the work material, owing to their low thermal conductivity and high chemical reactivity [1,2]. However, by properly selecting the tool material and cutting conditions an acceptable rate of tool wear may be achieved and thus lowering the total machining cost [3]. The performance of a cutting tool is normally assessed in terms of its life. Mostly, flank wear is considered, since it largely affects the stability of the cutting wedge and consequently the dimensional tolerance of the machined work surface [4]. The use of workpiece preheating (hot machining) as a technique for improving machining operations has been under consideration since the late 19th century. This was informed by understanding that metals tend to deform more easily when heated, thus enhancing machining. The principle behind hot machining is increasing difference in hardness of the cutting tool and workpiece, leading to reduction in the component forces, improved surface finish and longer tool life [5]. Amin and Talantov [6] studied the influence of the furnace method of preheating of workpiece on machinability of titanium alloy BT6 (Russian Standard) and found that the vertical cutting force component decreases with the increase in the preheating temperature but the radial and the axial components sharply increase to their peak values at a particular temperature. Ozler et al [7] used gas flame heating to improve the machinability of austenitic manganese steel. Wang et al [8] performed LAM using YAG continuous solid laser on Al2O3 particle reinforced aluminum matrix composite (Al2O3p/Al). The result of their study showed that in machining of Al2O3p/Al composite the cutting force was reduced by 30-50 %, tool wear was reduced by 20-30 % in laser assisted machining as compared with conventional cutting. Tosun and Ozler [9]studied hot machining in turning high manganese steels using liquid petroleum gas flame under different cutting conditions of feed rate, depth of cut, cutting speed and surface temperature and developed a mathematical model for tool life from the experimental data using a regression analysis method. The main objective of this study is to investigate the effect of workpiece preheating with high frequency induction heating on improvement of tool life of uncoated WC-Co inserts during end milling of titanium alloy Ti-6Al-4V. Tool wear, vibration, and cutting force were investigated during the experiments.